Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 7 - Rational Functions - 7.3 Multiplying and Dividing Rational Expressions - 7.3 Exercises: 21

Answer

$= -\frac{(3x+5)}{(x+2)} $ Frank thought that $(7-x) = (x-7)$, when in fact that is not true. Instead, Frank should have multiplied $(7-x)$ by $1=-1*(-1)$ to obtain $-1(x-7)$.

Work Step by Step

Frank thought that $(7-x) = (x-7)$, when in fact that is not true. Instead, Frank should have multiplied $(7-x)$ by $1=-1*(-1)$ to obtain $-1(x-7)$. $\frac{3x+5}{x-7} \times \frac{7-x}{x+2}$ $= \frac{(3x+5)(7-x)}{(x-7)(x+2)} $ $= \frac{(3x+5)(-(x-7))}{(x-7)(x+2)} $ $= \frac{-(3x+5)}{(x+2)} $ $= -\frac{(3x+5)}{(x+2)} $
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.